Terrestrial reptiles from San Lorenzo Island, Lima, Peru - Pérez Z., José (2015)
We report four species of terrestrial reptiles, a geckonid (Phyllodactlus cf. microphyllus), two lizards (Microlophus peruvianus and M. tigris) and one snake (Pseudalsophis elegans) from San Lorenzo island, Departament of Lima, Peru. Herein, we report the first record of “Loma’s lizard” M. tigris and the snake P. elegans in Peruvian islands. The presence of Lomas herbaceous and the considerable extent of San Lorenzo island can explain the relatively high species richness of terrestrial reptiles on the island.